Place and the politics of space in J.M.Coetzee’s life and times of Michael K - Teimouri, Mahdi (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2016)
The purpose of this paper is to show how space is manipulated in order to create order and control over people in a totalitarian regime. Michael, the protagonist of the novel, problematises hegemonic and totalising perception of space by occupying a position that rejects either/or logic of modern thought. Not only does Michael pose a threat to the arrogation of space by apartheid but also problematises the appropriation and control of identity and meaning which in totalitarian regimes are closely connected to the control of social spaces. Michael, for the most part, remains impervious to spatial and semantic disambiguation by resorting to the politics of ambivalence and in-betweenness. Such positionality makes the novel a platform for the demonstration of postmodern identity politics which hinges on a resistance to epistemological disambiguation and dualistic structuring. The framework used here consists of applying the theories of thinkers whose ideas share a penchant for disrupting the binary divisions that have underlain our socio-political understanding in the modern era. The novel will be analysed in light of these ideas to establish its compatibility with such a kind of reading.